Effects of protease supplementation on growth performance, blood constituents, and carcass characteristics of growing-finishing pigs - Min, Yejin (J Anim Sci Technol, 2019)
This experiment was conducted to evaluate the effects of dietary protease on growth performance, blood constituents, and carcass characteristics of growing-finishing pigs. A total of 48 growing pigs (initial body weight, 34.8 ± 0.62 kg) were randomly assigned to 2 dietary treatments (6 pigs/pen; 4 replicates/treatment). The treatments were a diet based on corn and soybean meal (CON) and CON supplemented with 0.01 % of protease (PRO). Pigs were fed respective dietary treatments with a 2-phase feeding program for 12 weeks. Pigs fed PRO had higher average daily gain (ADG; phase I, 866.38 vs. 821.75 g/d; overall, 910.96 vs. 866.30 g/d; p < 0.05) and gain to feed ratio (G:F; phase I, 0.345 vs. 0.363 g/g; p < 0.05) than those fed CON. However, there were no differences on blood constituents and carcass characteristics between CON and PRO of growing-finishing pigs. In conclusion, dietary protease supplementation in the typical diet for growing-finishing pigs improved growth rate.